ANALISIS KINERJA RANTAI PASOK AGROINDUSTRI KAKAO DI KABUPATEN LIMA PULUH KOTA, PROVINSI SUMATERA BARAT - Peni Shoffiyati, Melinda Noer, Rahmat Syahni, Asrinaldi (Jurnal Teknologi Industri Pertanian, 2019)
Implementation of supply chain management concepts is needed to meet consumer demand for agricultural products which include overall management of production, distribution and marketing processes that can be measured through the measurement of supply chain performance. Supply chain performance is the integration of supply chain activities, to enhance relationships to gain competitive advantage. Cocoa commodity is one of the leading commodities in West Sumatera, and Kabupaten Lima Puluh Kota is one of the locus of cocoa agroindustry. This study aimed to determine the supply chain system of cocoa agroindustry in Kabupaten Lima Puluh Kota in terms of material, information and financial flow of each involved actors, and to measure how the performance of the cocoa agro-industry supply chain in Kabupaten Lima Puluh Kota. The study used a questionnaire through the SCOR (Supply Chain Operation Reference) method with reliability, responsiveness, agility, cost and asset management attributes. The result of the research showed that in cocoa agro-industry supply chain there was a material flow of cocoa from farmer to cocoa processing agroindustry "Chokato", then processed cocoa products were sold to consumers (end consumers or consumers of IKM processing cocoa products). The information flow among actors included the quantity and price of cocoa that can be supplied and the quantity and price of processed cocoa products produced by cocoa processing agroindustry. In the financial flow, the value of purchases and sales value of magnitude were in line with the amount of material flow that exists between the actors in the supply chain system of cocoa agro-industry. The result of supply chain performance measurement was obtained that the highest importance level was at cost attribute equal to 4,84 in 1-5 scale meaning that in the supply chain of cocoa agrondustry was very important to the ability of supply chain entity in fulfillment of cost related to supply chain process, which will determine efficiency in product supply.Keywords: cocoa agroindustry, supply chain performance